Measurement of Physical Workload Ergonomic Risk Levels in Work Postures Using the Owas and Reba Methods at PLN UP3 Gresik - Nurul Hidayati; Hidayat Hidayat; Efta Dhartikasari Priyana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research was conducted at PLN UP3 Gresik to evaluate the sitting posture of employees and determine its alignment with ergonomic standards. The study aimed to improve employee posture to ensure a safer and more comfortable work environment. Sixteen workers participated in the study, which involved observations, interviews, and the distribution of questionnaires to identify issues related to work posture. The OWAS (Ovako Working Posture Analysis System) and REBA (Rapid Entire Body Assessment) methods were employed based on established literature. The findings revealed a mismatch between the design of tables and chairs and ergonomic requirements. According to the OWAS method, the work posture code was 2, indicating the need for corrective action. The REBA method showed angular values of 7 for group A, 4 for group B, and 8 for group C, all suggesting a need for improvement due to musculoskeletal complaints. Data were gathered through Nordic Body Map (NBM) questionnaires and photo analyses of workers' postures. The study concludes that corrective actions are necessary, recommending that the company design seats based on workers' anthropometric data and conduct periodic evaluations to ensure ongoing comfort and safety. Keywords: Ovako Work Analysis System (OWAS), Rapid Entire Body Assessment (REBA), Ergonomics, Work Posture Evaluation